2010
DOI: 10.1016/j.ijfatigue.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Response of a carbon-black filled SBR under large strain cyclic uniaxial tension

Abstract: A carbon-black filled SBR was submitted to various uniaxial tension cyclic tests in order to study its cyclic softening. Stress-softening and stretch creep were monitored during stretch-control tests and ratcheting tests, respectively. The material softening induced by cyclic loadings appeared to depend on the maximum loading applied. The cyclic amplitude or equivalently the cyclic energy did not affect the material softening. The latter experimental result draws our attention since it contrasts with former re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In the majority of studies involving fatigue of rubber, only the fatigue behavior in ambient (non-aggressive) environment is investigated. See for example the review of Mars and Fatemi [9] and the work of Verron and Andriyana [10], Andriyana et al [11], Brieu et al [12] among others. However, considerably fewer studies which explicitly deal with the fatigue failure analysis of rubber in aggressive environments are available [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of studies involving fatigue of rubber, only the fatigue behavior in ambient (non-aggressive) environment is investigated. See for example the review of Mars and Fatemi [9] and the work of Verron and Andriyana [10], Andriyana et al [11], Brieu et al [12] among others. However, considerably fewer studies which explicitly deal with the fatigue failure analysis of rubber in aggressive environments are available [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The fenders used in commercial docks, ports, and harbors are mostly fabricated from rubber because of its outstanding performances, like low transmission force and excellent energy absorption capacity. In addition, rubber has many more favorable properties such as high flexibility, good resilience, a long service life [1][2][3][4][5][6], an excellent resistance toward temperature [6][7][8][9][10][11][12], saltwater [13,14], and other environmental factors [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Poisson 9 studied the influence of the strain ratio on the uniaxial fatigue life of chloroprene and observed that the fatigue life increased with the increase in average stress at high strain ratio ( R > 0.2). Brieu 10 tested SBR‐filled rubber by uniaxial tensile cycling and found that the rubber material exhibited a cyclic softening characteristic with a significant Mullins effect, where the softening of the material caused by cyclic loading appeared to depend on the maximum load applied, but the cyclic amplitude or equivalent cyclic energy had no effect on the softening. Many scholars have also observed this phenomenon in fatigue tests of rubber materials 11–14 .…”
Section: Introductionmentioning
confidence: 99%